Innovation in Mathematics Learning Through Discovery Learning and Flashcard Media in Elementary Madrasahs - Rohmah, Indah Ainur; Prayogo, Muhammad Suwignyo; Almasi, Mustapha (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
Mathematics learning in Madrasah Ibtidaiyah often faces significant obstacles due to a lack of interest and motivation in learning among students. This is often associated with using traditional and less interesting teaching methods, which do not meet students' basic psychological needs. To overcome this problem, this study used qualitative methods and purposive sampling to select respondents according to the study's needs. Data were collected through passive observation, semi-structured interviews, and documentation techniques, which were then analyzed using an interactive analysis model. This process facilitated an in-depth evaluation of the impact of using the Discovery Learning model supported by flashcard media. The results of this study indicate an increase in student engagement and motivation with the implementation of the Discovery Learning model and flashcards, characterized by increased interaction during learning sessions and a better understanding of mathematical concepts. Based on these results, it is recommended that educators integrate interactive and student-centered teaching methods, such as Discovery Learning, to increase engagement and motivation in learning mathematics. Further research is needed to explore the long-term impact of this pedagogical approach on student learning outcomes and satisfaction by comparing it with traditional teaching methods. This study's contribution is to prove that the Discovery Learning method and the use of flashcards are effective in increasing students' mathematical engagement and understanding. This supports the use of more interactive learning approaches to increase learning motivation. In addition, this study recommends further studies to assess the long-term impact of this method compared to traditional teaching, providing an important contribution to future educational research.